2013
DOI: 10.1105/tpc.113.111724
|View full text |Cite
|
Sign up to set email alerts
|

MTV1 and MTV4 Encode Plant-Specific ENTH and ARF GAP Proteins That Mediate Clathrin-Dependent Trafficking of Vacuolar Cargo from the Trans-Golgi Network

Abstract: Many soluble proteins transit through the trans-Golgi network (TGN) and the prevacuolar compartment (PVC) en route to the vacuole, but our mechanistic understanding of this vectorial trafficking step in plants is limited. In particular, it is unknown whether clathrin-coated vesicles (CCVs) participate in this transport step. Through a screen for modified transport to the vacuole (mtv) mutants that secrete the vacuolar protein VAC2, we identified MTV1, which encodes an EPSIN N-TERMINAL HOMOLOGY protein, and MTV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 100 publications
5
64
0
Order By: Relevance
“…This indicates that VSRs present in isolated plant CCVs (Kirsch et al, 1994;Hinz et al, 1999;Sauer et al, 2013) are derived from Golgi/TGN membranes, the site of action for AP1 complexes (Park et al, 2013). The lack of interaction between the VSR tail and PM-specific AP2 argues against the recently suggested endocytic origin of VSR-containing CCVs (Scheuring et al, 2011).…”
Section: Post-er Targeting Of Plant Vsrs Depends On the Adaptor Complmentioning
confidence: 98%
“…This indicates that VSRs present in isolated plant CCVs (Kirsch et al, 1994;Hinz et al, 1999;Sauer et al, 2013) are derived from Golgi/TGN membranes, the site of action for AP1 complexes (Park et al, 2013). The lack of interaction between the VSR tail and PM-specific AP2 argues against the recently suggested endocytic origin of VSR-containing CCVs (Scheuring et al, 2011).…”
Section: Post-er Targeting Of Plant Vsrs Depends On the Adaptor Complmentioning
confidence: 98%
“…EDR4-GFP appears to localize on the plasma membrane and on dot-like intracellular structures in the cytosol. To determine the subcellular localization of EDR4, we assessed the colocalization of EDR4-GFP with several organelle markers, including mCherry-SYP61 (TGN/EE), ARA6-mCherry (late endosome), SYP32-mCherry (cis-Golgi), and HDEL-mCherry (ER) (Nelson et al, 2007;Geldner et al, 2009;Innes, 2011, 2012;Sauer et al, 2013), and examined EDR4-GFP in root tips of transgenic plants. Microscopy and quantification analysis showed that a large portion of EDR4-GFP protein overlapped with the TGN/EE marker SYP61, the late endosome marker ARA6, and the cis-Golgi marker SYP32, but a smaller portion of EDR4-GFP overlapped with the ER marker HDEL ( Figures 3A to 3E).…”
Section: Edr4 Mainly Localizes At the Plasma Membrane And Endosomal Cmentioning
confidence: 99%
“…The third main group contains proteins that have an N terminus with structural similarity to the VHS domain of human Hrs1 and additionally contain a GGA domain. In addition to these three main groups, there are two outliers: AT3G61800 and the recently described MTV1/AT3G16270 (Sauer et al, 2013). These are single genes in Arabidopsis, but they are conserved throughout the plant lineage with homologs found even in ancestral plants.…”
Section: Phylogenetic Analysis Of Enth/anth/vhs Proteinsmentioning
confidence: 99%
“…Nevertheless, its N terminus bears all hallmarks of an ENTH domain; indeed, before its functional characterization, MTV1 was subjected to structural NMR analysis (López-Méndez et al, 2004), and a comparison to known protein structures using Phyre2 reveals human Enthoprotein as the best scoring hit. A screen for mutants impaired in vacuolar transport (Sanmartín et al, 2007) identified a mtv1 loss-of-function mutant, and MTV1 was characterized functionally and biochemically (Sauer et al, 2013). Loss of MTV1 leads to mis-sorting of several endogenous and chimeric vacuolar marker proteins, which instead are secreted to the extracellular space.…”
Section: Mtv1: a Plant Outsider?mentioning
confidence: 99%
See 1 more Smart Citation